Apoyo en supervisión y control de actividades de obras civiles en Cermont S.A.S, Arauquita-Arauca (2023)
In this research, the topic of supervision and control of civil works activities in the company CERMONT S.A.S was addressed, which aims to present quality works in compliance with established times and standards. Support for the improvement and adaptation of the Alcides Ceballos sports center in the municipality of Arauquita, consists of the construction of a finished skating rink. To solve some specific problems presented during the internship, a mixed approach methodology was implemented, since it is intended to support the monitoring of the work through field visits and photographic recording, calculate the quantities of work through calculation reports using the appropriate formulas for a specific case. Finally, the preparation of technical specifications documents and construction processes.